The Influence of Work Abilities on Employee Performance at The Binjai City Tourism Office - Juwita, Wira; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The aim of this research is to determine and analyze the influence of work ability on employee performance at the Binjai City Tourism Office. This research was conducted using a causal associative quantitative approach. The sample used was all company employees, with a total of 38 people. The research results show that work ability has a positive and significant effect on employee performance. This is shown by the T-count value of3.756 which is greater than the T-table 1.685, and the P-Value value is 0.000 which is smaller than 0.05. The regression coefficient shows that if work ability is increased by 1 unit, employee performance will increase by 0.931 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.221 or 22.10%, which indicates that work ability has a low influence on employee performance, while the remaining 77.90% is influenced by other factors that have not been studied. Thus, partially, work ability has a positive and significant effect on employee job satisfaction at the Binjai City Tourism Office. This identifies that, meaning, improvements in employee work abilities can contribute to improving employee performance.